Making girls and boys inside the science of sex - McCredie, Jane.; ebrary, Inc. (Sydney : University of New South Wales Press, 2011)
Is gender really as strightforward as we would like to think? What is it that makes a person a man or woman? Leading us on a journey from chromosones to evolutionary psychology and through to the playground Jane McCredie explores these fascinatiang questions unfolding the story of gender.
Includes bibliographical references (p. 201-207) and index.
Electronic reproduction.
Keywords: Gender identity; Sex (Psychology); Sex determination, Genetic; Electronic books